Reading Martin Amis’s Recreation of the Perpetrator’s Gaze in The Zone of Interest - Aída Díaz Bild (Miscelánea: A Journal of English and American Studies)
The Zone of Interest is a historical novel set in Auschwitz in the months from August 1942 to April 1943, and which belongs to the category of perpetrator fiction. This article centres on the character of Paul Doll, the camp commandant, who represents the banality of evil and, through whose voice Amis gives the readers a sharp picture of the abominations committed by the Nazis, while he recounts the causes and devastating consequences of the perpetrators’ actions. By transforming Doll into a buffoon, Amis offers a different perspective on the Holocaust and makes the reader realise that those responsible for the worst crimes were neither monsters nor exceptional human beings, but normal, vulnerable people who had the fate of millions of Jews in their hands.